A comprehensive analytical study of sludge from water reclamation plants in Singapore for advanced thermochemical conversion processes - Chan, Wei Ping (2017)
Recently sludge attracted great attentions as a potential feedstock for advanced thermochemical conversion processes. Cheap heterogeneous waste mixtures could be converted into valuable products such as pyrolysis oil, synthetic gases and char. However thermal degradation behaviours of sludge were complex and distinctive therefore causing significant challenges in engineering design and system optimisation. In this study, sludge samples were collected based on type, plant, and batch categorisation from Water Reclamation Plants in Singapore. Existing and proposed analytical methods were applied. Synthetic sludge was formed based on compositions analytical procedure and simulation study developed to address issues in kinetics and conversion study. Qualitative similarities, quantitative variations, and correlations of thermochemical properties with compositions of sludge were identified. Oxidation of inorganics caused deviations on characterisation which could be reduced by alternative parameters and comparison bases proposed. Degradation behaviours of sludge were also found to be varied according to operating conditions and its intrinsic characteristics.